Estimation of historical control rate for a single arm de-escalation study – Application to the POSITIVE trial. (October 2020) - Sun, Zhuoxin; Niman, Samuel M.; Pagani, Olivia; Partridge, Ann H.; Azim, Hatem A.; Peccatori, Fedro A.; Ruggeri, Monica; Di Leo, Angelo; Colleoni, Marco; Gelber, Richard D.; Regan, Meredith M.; ,
Abstract : Background: Although randomized controlled clinical trials are optimal to evaluate the effect of an experimental therapy, single-arm trials are required whenever randomization is unethical or not feasible, such as de-escalation studies. We propose using prospectively identified historical controls to place results of single-arm, de-escalation trials into context. Methods: POSITIVE is a prospective, single-arm study in young women with hormone-receptor-positive early breast cancer to determine if temporarily interrupting adjuvant endocrine therapy in order to become pregnant increases the risk of a breast cancer event. After 272 women enrolled in POSITIVE, we identified a cohort of 1499 SOFT/TEXT patients potentially eligible to enroll in POSITIVE who did not interrupt endocrine therapy. Method I used the SOFT/TEXT cohort to calculate annualized hazard rates by a piecewise exponential model. Method II used the SOFT/TEXT cohort to group-match SOFT/TEXT patients to POSITIVE patients; sample sets of SOFT/TEXT patients were randomly drawn 5000 times to obtain sets having patient, disease, and treatment characteristics more balanced with POSITIVE participants. Results: Compared with SOFT/TEXT, POSITIVE participants were younger, less likely to be overweight/obese, had fewer positive nodes, and fewer received aromatase inhibitor or chemotherapy. The estimated 3-year breast cancer free interval event rates were 9.5% (95% CI: 7.9%, 11.1%) for Method I and 9.4% (95% CI: 7.8%, 10.9%) for Method II, compared with 5.8% initially assumed when POSITIVE was designed. Conclusion: External control datasets should be identified before launching single-arm, de-escalation trials and methods applied during their conduct to provide context for interim monitoring and interpretation of the final analysis. Highlights: Prospective identification of external historical controls for single-arm studies. Statistical methods for estimating historical control rates for single-arm studies. Methods applied for interim monitoring and final analysis of the POSITIVE study.